Health behaviors of academic youth during the COVID-19 pandemic (Contemporary problems of physical and health culture, 2022)
The questionnaire survey was conducted among students of MA studies in pedagogy, the total number of respondents is 160 people. The results of the research show that the motivation to be active during the pandemic has decreased, and too long using the computer causes increased health ailments. Most students are aware of leading a bad lifestyle and the need to quickly change their habits, but they wait for stimuli and encouragement from their peers, are reluctant to actively organize their time themselves, and wait for organized classes.